Bridging Theory and Practice: Challenges in Clinical Skill Application Among Radiology Technology Trainees in Ethiopia - Alo Edin; Ashenafi Abraha; Yenuse Molla; Takala Utura; Angefa Ayele (Journal of Medical Education and Curricular Development)
Background The goal of clinical practice is to bridge the gap between theory and practice by preparing students to apply their classroom-based knowledge and skills to real patient situations. However, clinical practice faces many challenges based on the setting and infrastructure of the country's clinical learning environment. This qualitative study focused to explore the challenges faced by Medical Radiology technology students and instructors during clinical practice at Hawassa University. Methods A qualitative exploratory approach was conducted from June 15, 2022, to July 15, 2022. The participants consisted of 28 medical radiology technology students and 8 medical radiology technology instructors. The participants were selected using a purposive sampling technique, and data were collected using semi-structured open-ended questions. Focus group discussions and in-depth interviews were audio-recorded, and notes were also taken. The audio-recorded data were transcribed, translated, coded, categorized, and conceptualized into 4 major themes using thematic analysis and ATLAS ti.7. Results In the study, we conducted a thematic data analysis to identify 4 key themes that emerged from the data. The findings revealed that department-related factors, clinical learning environment factors, clinical supervision-related issues, and poor pedagogical approaches negatively impacted the clinical experiences of radiology technology trainees. Conclusion The study revealed significant challenges faced by radiology technology students during clinical practice in the study area. These included insufficient supervision, disorganized training, inadequate equipment, and overcrowded clinical settings. To enhance students’ clinical competence and future radiography skills, the curriculum and clinical training model should be revised to better integrate theory and practice. Establishing supportive clinical learning environments through improved supervision, structured protocols, adequate equipment, and reasonable patient loads is crucial for developing radiographers who can use radiology technology equipment safely and appropriately.